Transformasi Desa Melalui Literasi: Pendekatan Diskusi Buku - Prasetia, Anggi (Ngarsa: Journal of Dedication Based on Local Wisdom, 2024)
Literacy remains a serious issue in society. This condition is evident from empirical observations, such as limited reading interest, inadequate critical thinking skills, weakened social connections, and persistent barriers to accessing knowledge. This community service activity aims to improve the quality of life through enhanced literacy. Specifically, the objectives are to raise awareness and interest in reading, develop critical thinking skills, and expand access to knowledge for the community. The method employed in this activity was Participatory Action Research (PAR), involving active community participation at every stage. These stages include identifying relevant literacy themes, jointly planning the format and schedule of discussions, and conducting inclusive implementation. This process is followed by collective reflection to evaluate the effectiveness of the activities and to design follow-up actions initiated by participants, such as activities based on the outcomes of book discussions. The results of this activity indicate an improvement in the critical literacy skills of the community. The book discussions created an inclusive dialogical space, strengthening analytical thinking, communication, and collaboration skills. The activity contributed to building social capital by fostering an active learning community, enhancing a sense of togetherness, and raising collective awareness of significant issues. In the long term, this activity could encourage local initiatives to expand literacy access and address community challenges, thereby supporting sustainable community empowerment. Keywords: Village community empowerment, Strengthening literacy, Book discussion  Abstrak: Literasi masih menjadi masalah serius masyarakat. Hal ini terlihat dari aspek empiris, seperti rendahnya minat baca, kurangnya kemampuan berpikir kritis, melemahnya hubungan antaranggota masyarakat, serta kuatnya sekat-sekat sumber pengetahuan yang membatasi akses informasi. Tujuan kegiatan pengabdian ini adalah untuk meningkatkan kualitas hidup masyarakat melalui peningkatan literasi. Secara spesifik, kegiatan ini bertujuan untuk meningkatkan kesadaran dan minat baca, mengembangkan keterampilan berpikir kritis, serta memperluas akses masyarakat terhadap pengetahuan. Metode pengabdian ini menggunakan pendekatan Participatory Action Research (PAR), yang melibatkan partisipasi aktif masyarakat dalam setiap tahap. Tahapan tersebut meliputi identifikasi tema literasi yang relevan, perencanaan bersama mengenai format dan jadwal diskusi, hingga pelaksanaan yang inklusif. Proses ini diikuti oleh refleksi kolektif untuk mengevaluasi efektivitas kegiatan dan merancang tindakan lanjutan yang diinisiasi oleh peserta, seperti kegiatan berbasis hasil diskusi buku. Hasil kegiatan ini menunjukkan peningkatan kemampuan literasi kritis masyarakat. Diskusi buku berhasil menciptakan ruang dialog yang inklusif, memperkuat keterampilan berpikir analitis, komunikasi, dan kolaborasi. Kegiatan ini berkontribusi membangun modal sosial dengan menciptakan komunitas pembelajar yang aktif, meningkatkan rasa kebersamaan, dan memunculkan kesadaran kolektif terhadap isu-isu penting. Dalam jangka panjang, kegiatan ini mampu mendorong inisiatif lokal untuk memperluas akses literasi dan menyelesaikan permasa-lahan komunitas, sehingga mendukung pemberdayaan masyarakat secara berkelanjutan. Kata kunci: Pemberdayaan masyarakat desa, Penguatan literasi, Diskusi buku